СХІДНА ЄВРОПА В КОНЦЕПЦІЯХ ТА ПРАКТИЦІ ЗОВНІШНЬОЇ ПОЛІТИКИ США В УМОВАХ БІПОЛЯРНОГО СВІТУ (Zaporizhzhia Historical Review, 2020)
The article is devoted to the analysis of main doctrines and conceptions of the US-EastEuropean policy at the period of the Cold War. The author consistently proves that this one was closely connected with the US policy towards the Soviet Union and was of a minor importance in American system of foreign policy priorities at that time.